Insulinotropic effect of Teucrium polium; Identification of potential mechanistic drug targets - Mannan, Adnan; Helmerhorst, Erik; Carlessi, Rodrigo; Caccetta, Rima (Net Journals, 2024)
Teucrium polium (T. polium), commonly known as golden germander, is a herb that grows in the Mediterranean region and is used by the locals to treat diabetes mellitus. The glucose-lowering effect of T. polium is well established in rodents. This study aims to examine whether the glucose-lowering effect is by inducing the release of insulin from pancreatic beta cells and to identify key measurable biomolecules/sites that are modified in the lead-up to insulin release. Insulin secretion was examined in BRIN-BD11 pancreatic beta cells treated with T. polium extract in vitro and key flavonoids were identified using LCMS. The T. polium extract promoted increased insulin secretion (p<0.05), in a dose-dependent manner, and increased glucose uptake (p<0.05) within 30min. This was accompanied by an increase in GLUT2 (p<0.05) and glucokinase (p<0.01) expression. Also, mitochondrial metabolism and glycolytic rates were enhanced (p<0.05), and ATP production increased (p<0.01), which coincided with increased (p<0.01) calcium influx. Rutin and apigenin were detected, but not quercetin, in this extract. T. polium promotes insulin secretion. T. polium does this by GLUT2 and glucokinase expression, increased glucose transport, metabolism and ATP production, ultimately increasing intracellular calcium.